Gambaran Pelaksanaan Program Observasi STOP dan Analisis Penyebab Adanya Tindakan Tidak Aman dan Kondisi Tidak Aman pada Perusahaan Pembangkit Listrik Tenaga Uap di Jawa Timur - Pebriana Anggun Lisa Putri; Denny Ardyanto Wahyudiono; Endang Dwiyanti; Alifiah Rizky Rosydah; Ahmad Imaduddin (Media Gizi Kesmas, 2023)
Background: Work accidents are generally caused by unsafe acts and unsafe conditions. The STOP observation program (Safety Training Observation Program) is a form of Behavior Based Safety (BBS) with the focus being observed on human factor. In practice, what is done is to analyze the reasons workers do, and apply it with the aim to improve their behavior towards safe actions.   Objectives: This study aims to study the implementation of the STOP observation program and the causes of unsafe acts and unsafe conditions at a Steam Power Plant Companies (PLTU) in East Java. Methods: This research was a descriptive observational study, with a cross sectional approach. The data used in this study were sourced from observations of the work environment, interviews with resource persons and company secondary data. The data analysis used in this research is qualitative. Results: The STOP observation program was carried out by all workers with two-way communication. In 2020 there were 639 observers, while in 2021 there are 2,321 observers. In 2020 there were 4,212 unsafe acts (1.51%) and in 2021 there were 8,226 unsafe acts (1.65%). Meanwhile, there were 1,878 (2.56%) for unsafe conditions in 2020 and 2,512 (1.71%) in 2021. Conclusions: The implementation of STOP observations had been going quite well, there is an increase in observations, but unsafe actions and conditions are still found in the work process.